Political Advertising in General Elections - Rais Harahap, Amin; Katimin, Katimin; Efendi Samosir, Hasrat (International Journal of Science and Environment (IJSE), 2025)
This study aims to analyze the role and influence of political advertising in Indonesia’s general elections, focusing on how it shapes public opinion, sets the political agenda, and frames candidate images. Utilizing Political Communication Theory, Agenda Setting Theory, and Framing Theory as the theoretical framework, the research explores the strategic use of political advertisements across traditional and digital media platforms. Employing a qualitative approach through literature review and content analysis, the study examines secondary data from academic journals, official election reports, legal regulations, and media publications. The analysis reveals that political advertising in Indonesia functions not merely as a promotional tool but as a strategic instrument to influence voter perceptions and behavior, prioritizing certain political issues while framing narratives that align with candidates’ desired images.Findings show that while political ads effectively elevate issues like the economy and corruption in public discourse, they often emphasize candidate personalization and emotional appeals over substantive policy discussions. The rise of digital media and microtargeting techniques further intensifies the reach and segmentation of political messages, raising concerns about misinformation and social polarization. The study concludes that effective political advertising integrates message credibility, media channel selection, agenda-setting, and framing strategies tailored to the socio-political context. It underscores the need for adaptive regulatory frameworks to ensure transparency and fairness in political communication, thereby contributing to a more informed electorate and healthier democratic processes in Indonesia.